SubMachine: Web‐based tools for exploring seismic tomography and other models of Earth's deep interior - Hosseini, K; Matthews, K; Sigloch, K; Shephard, G; Domeier, M; Tsekhmistrenko, M (American Geophysical Union, 2018)
We present SubMachine, a collection of web‐based tools for the interactive visualization, analysis, and quantitative comparison of global‐scale data sets of the Earth's interior. SubMachine focuses on making regional and global‐scale seismic tomography models easily accessible to the wider solid Earth community, in order to facilitate collaborative exploration. We have written software tools to visualize and explore over 30 tomography models—individually, side‐by‐side, or through statistical and averaging tools. SubMachine also serves various nontomographic data sets that are pertinent to the interpretation of mantle structure and complement the tomographies. These include plate reconstruction models, normal mode observations, global crustal structure, shear wave splitting, as well as geoid, marine gravity, vertical gravity gradients, and global topography in adjustable degrees of spherical harmonic resolution. By providing repository infrastructure, SubMachine encourages and supports community contributions via submission of data sets or feedback on the implemented toolkits.